Natural infection of Lutzomyia longipalpis (Cembrene-1 population) with Leishmania infantum in a new visceral leishmaniasis focus in the eastern region of São Paulo State, Brazil. - da Silva, Mariana Dantas (Rev Soc Bras Med Trop, 2021)
INTRODUCTION: Visceral leishmaniasis (VL) transmission has been associated with two different populations of the Lutzomyia longipalpis complex in São Paulo state. METHODS: In a recent focus of VL, we captured and dissected sand flies and investigated Leishmania infantum infection by parasitological, PCR, and sequencing analysis. RESULTS: Flagellates were observed in 2 of 47 (4.2%) cembrene-1 Lu. longipalpis females. The sequences obtained matched those of Le. infantum. CONCLUSIONS: We found that the transmission of Le. infantum by cembrene-1 females may occur at a high rate in this focus of VL and presented new data on the vector capacity of this population.